1991
DOI: 10.1111/j.1360-0443.1991.tb03422.x
|View full text |Cite
|
Sign up to set email alerts
|

In‐patient withdrawal from long‐term benzodiazepine use

Abstract: Twenty-one patients completed an intensive in-patient and out-patient group-based programme, to achieve withdrawal from long-term benzodiazepine dependence. By 6-month follow-up (post-withdrawal), eight patients (38%) had achieved a 'good' outcome. Generally, patients demonstrated moderate levels of psychiatric morbidity and depression in the pre-withdrawal phase; a diagnosis of a depressive disorder being associated with either an 'intermediate' or 'poor' outcome in comparison to patients receiving a diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…On average the CSG sample showed a broadly normal psychological profile with low-tomedium anxiety scores and low levels of depression (Table 1). Self-efficacy skills in F1: Pride and Coping, F2: Expectations in Interpersonal Situations and F3: Life Control, were higher than the norms previously obtained from a general sample of the local population (Joughlin et al, 1991) but self-esteem appeared lower, resulting in a mean total score slightly lower than the norms.…”
Section: Psychological Factorscontrasting
confidence: 78%
See 1 more Smart Citation
“…On average the CSG sample showed a broadly normal psychological profile with low-tomedium anxiety scores and low levels of depression (Table 1). Self-efficacy skills in F1: Pride and Coping, F2: Expectations in Interpersonal Situations and F3: Life Control, were higher than the norms previously obtained from a general sample of the local population (Joughlin et al, 1991) but self-esteem appeared lower, resulting in a mean total score slightly lower than the norms.…”
Section: Psychological Factorscontrasting
confidence: 78%
“…Depression: > I 2 (high), 4-12 (medium), < 9 (low). Self-efficacy: Normative values for the Tooting Population (Joughlin, 1991) F1, range 12.94-17.78, mean 15.91; F2, range 10.32-11.72, mean 10.89; F3, range 10.56-13.56, mean 12.07; F4, range 8.17-10.53, mean 9.72. attended week 1 and week 6 of the weight loss programme.…”
Section: Operation Of the Groupsmentioning
confidence: 99%
“…[8] described 3/5 MMT patients who were successfully detoxified from alprazolam with phenobarbitol, but they had no or only minimal follow‐up. Another study [9] in which the investigators used a very intensive inpatient BZD‐tapered discontinuation procedure reported a 67% success rate at 6 months. Using clonazepam as a tapering agent for 37 patients treated with alprazolam for anxiety disorders, Patterson [12] reported a 100% success rate at 1 month follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has been done on treatment modalities for BZD dependence and even less on BZD‐dependence treatment in heroin addicts or MMT patients. Most investigations have centred on the tapered detoxification of BZD with [8] or without [9] substitution by a barbiturate (e.g. phenobarbitol) or a long‐acting BZD (e.g.…”
mentioning
confidence: 99%
“…Some of these patients feel less anxious once BZDs have been withdrawn, 104,105,139 while others experience a recurrence of anxiety. Table 4 summarizes the percent of patients referred to BZD discontinuation clinics who ultimately remained symptom‐free once tapered 23,104,105,139,173−178 . From this data, it appears that roughly 40% to 50% of patients maintained on long‐term BZD therapy are either no longer deriving clinical benefit or can be successfully treated with an alternative anxiolytic agent.…”
Section: Benzodiazepine Dependencementioning
confidence: 99%